A comprehensive review of secondary metabolites from the genus Agrocybe: Biological activities and pharmacological implications - Liqiu Zhang; Meixia Yan; Chengwei Liu (Mycology, 2024)
ABSTRACTThe genus Agrocybe, situated within the Strophariaceae family, class Agaricomycetes, and phylum Basidiomycota, encompasses a myriad of species exhibiting significant biological activities. This review presents an integrative overview of the secondary metabolites derived from Agrocybe species, elucidating their respective biological activities and potential pharmacological applications. The metabolites under scrutiny encompass a diverse array of biological macromolecules, specifically polysaccharides and lectins, as well as a diverse group of 80 documented small molecular chemical constituents, classified into sterols, sesquiterpenes, volatile compounds, polyenes, and other compounds, their manifesting anti-inflammatory, anticancer, antioxidant, hepatoprotective, antimicrobial, and antidiabetic activities, these metabolites, in which polysaccharides exhibit abundant activities, underscore the potential of the Agrocybe genus as a valuable source of biologically active natural products. The present review emphasises the need for escalated research into Agrocybe, including investigations into the biosynthetic pathways of these metabolites, which could foster the development of novel pharmaceutical therapies to address various health challenges.